Tumor pseudoprogression and true progression following gamma knife radiosurgery for recurrent ependymoma. Issue 5 (May 2016) - Wu, Chih‐Chun; Guo, Wan‐Yuo; Chung, Wen‐Yuh; Wu, Hsiu‐Mei
Abstract : Background : Gamma knife radiosurgery (GKRS) has become an effective salvage therapeutic option for recurrent ependymomas. However, its effectiveness can be assessed only by neuroimaging before clinical deterioration occurs. We analyzed the evolution of post‐GKRS magnetic resonance imaging (MRI) features and sought to establish the feasibility of timely appropriate clinical management of the recurrent tumors. Methods : We retrospectively investigated 19 recurrent ependymomas of 11 patients treated with GKRS in our hospital from 1994 to 2013. All included tumors had sequential MRI at 3–6‐month intervals, and tumor response was volumetrically calculated on consecutive MRI. Results : Post‐GKRS tumors might show an increased enhancement or loss of enhancement associated with tumor enlargement or straight shrinkage. Seven of 19 tumors (37%) had continuously regressed or remained stable up to the last follow‐up. Twelve of 19 tumors (63%) showed enlargement of enhancing lesions through examination of the post‐GKRS follow‐up MRI within the first 18 months. Five of 12 tumors (42%) showed continuous enlargement, which was interpreted as true progression; seven of 12 (58%) exhibited transient increasing enhanced volume that resolved within 6 months, and which was interpreted as pseudoprogression. There was no significant association between the presence of pseudoprogression and the pathological grades or locations of the tumors, and the concomitant chemotherapy or previous radiotherapy. Statistically significant differences were found for mean apparent diffusion coefficient (ADC) values and ADC ratio (prior to and after GKRS) of enhancing lesions between pseudoprogression and true progression. Conclusion : The MRI patterns of post‐GKRS recurrent ependymomas are heterogeneous. Transient increased tumor volume may represent pseudoprogression, whose final tumor control rate was not significantly different from those cases with straight tumor shrinkage. ADC values, ADC ratio, and sequential follow‐up MRI scans are beneficial to differentiate between pseudoprogression and true progression, and help guide clinical management.